A rare case of adult scalp pyoderma gangrenosum with cranial osteolysis. (March 2018) - Aljohmani, L.; Abdul-Jalil, K.; deBlacam, C.; Murphy, G.M.; O'Sullivan, J.B.
Abstract: Pyoderma gangrenosum (PG) is a rare and painful idiopathic skin condition that has one or more areas of chronic ulceration with well demarcated and undermined borders. Bone osteolysis (the pathological destruction of bone tissue) secondary to PG is a rare phenomenon with limited cases reported in children only. This is the first case report of scalp PG with cranial osteolysis in an 80-year-old adult, with an initial presentation mimicking skin carcinoma. This case highlights the importance of a multidisciplinary team (MDT) meeting discussion, diagnosis of PG by exclusion and the successful treatment of this patient's PG eroding to the bone.